ANALISIS DETERMINASI RASIO KEUANGAN DAN INFLASI TERHADAP RETURN SAHAM - Rolia Wahasusmiah; Endang Puji Lestari; Poppy Indriani; Septiani Fransisca (Fakultas Ekonomi Universitas IBA, 2022)
This study aims to determine and analyze the factors that influence stock returns in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange. These factors consist of liquidity, profitability, accounting profit, cash flow, inflation, and leverage. The population in this study were 19 manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX). Sampling in this study using the purposive sampling method was used to determine the research sample so that 13 samples of companies or 65 units of data analysis were obtained at manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Data analysis in this study using multiple linear regression. The results showed that the accounting profit variable and the inflation variable had a positive effect on stock returns. Then the leverage and cash flow variables have a negative effect on stock returns, while the liquidity and profitability variables have no effect on stock returns.